THU0506 MAST CELL DEFICIENCY AMPLIFIES INFLAMMATORY RESPONSE IN A MOUSE MODEL OF KAWASAKI'S DISEASE. (June 2019) - Springer, Jason; Zhang, Mingcai; Funk, Ryan; Tawfik, Ossama; Ohno, Naohito; Miura, Noriko; Maz, Mehrdad; Dileepan, Kottarappat
Abstract : Background: Kawasaki's disease is a pediatric medium vessel vasculitis causing coronary arteritis and potentially coronary artery aneurysms. Higher systemic levels of Interleukin-6 (IL-6) in the first week of disease has been shown to be associated with a higher risk of coronary artery aneurysms (1, 2 ). Mice injected with Candida albicans water-soluble fraction (CAWS) develop coronary and aortic arteritis like that seen in Kawasaki's disease. Our prior work has demonstrated that mast cell degranulation can inhibit lipopolysaccharide (LPS)-induced IL-6 gene expression in the aorta and systemic IL-6 production (3 ). Objectives: The objective of this study was to determine if mast cells play a role in the IL-6 homeostasis in an established mouse model of Kawasaki's disease (CAWS model). Methods: 8-10-week-old male wild type controls (WT) and kitW-sh/W-sh mice (mast cell deficient, MCD) of C57Bl/6 background were randomly distributed into four groups (WT-PBS, WT-CAWS, MCD-PBS, MCD-CAWS). They were either injected intraperitoneally with PBS or CAWS (2 mg/mouse) daily for a period of 5 days. Eight animals from each group were sacrificed at either 7, 14 or 30 days after the last injection and blood, aorta and heart specimens were harvested. A pathologist (OT), blinded to treatment groups, examined aortic root and adjacent myocardium specimens and assigned a score for the degree of inflammation (0-6). Results: Seven MCD-CAWS mice died unexpectedly within 24 hours of the first CAWS injection. Autopsies reviewed marked liver sinusoidal dilation in all and patchy necrosis of the liver in 4. Similar, liver findings were seen in 75% of MCD-CAWS after 7 days, but not in other groups. MCD-CAWS mice had higher systemic IL-6 compared to WT-CAWS at both 7 days (208± 21 vs 152 ± 12 pg/ml; p<0.001) and 14 days (226 ± 49 vs 169 ± 19 pg/ml; p=0.04), but not at 30 days. By 14 days mice in MCD-CAWS had significantly higher serum INFγ compared to WT-CAWS mice (97 ± 4 vs 87 ± 7 pg/ml, p=0.0086) which remained persistently elevated even at 30 days (103±8 vs 91±4 pg/ml; p=0.002). TNFα was higher in MCD-CAWS compared to WT-CAWS at 7 days (258 ± 8 vs 243 ± 6.5 pg/ml, p=0.0016), 14 days (266± 14vs 239 ± 6pg/ml, p<0.001) and 30 days (326±52 vs 256±8 pg/ml, p=0.002). The average aortic root inflammatory score was non-significantly higher in the MCD-CAWS group compared to WT-CAWS at both 7 days (1.5 vs 1.3) and 14 days (3.7 vs 2.4). Conclusion: Mast cell deficiency resulted in higher systemic levels of IL-6, TNFα and INFγ in the CAWS mouse model of Kawasaki's disease. Similarly, mast cell deficiency resulted in more intense inflammation at the root of the aorta in this model. These results support the novel concept that mast cells play a protective role in reducing the initial systemic inflammatory response in Kawasaki's disease. References: [1] Ueno Y, Takano N, Kanegane H, Yokoi T, Yachie A, Miyawaki T, et al. The acute phase nature of interleukin 6: studies in Kawasaki disease and other febrile illnesses. Clinical and experimental immunology. 1989;76(3):337-42. [2] Chow YM, Lin CY, Hwang B. Serum and urinary interleukin-6 (IL-6) levels as predicting factors of Kawasaki disease activity. Zhonghua Minguo xiao er ke yi xue hui za zhi [Journal] Zhonghua Minguo xiao er ke yi xue hui. 1993;34(2):77-83. [3] Springer J, Raveendran V, Smith D, Maz M, Dileepan K. OP0138 Novel Role of Mast Cells in the Regulation of Large Vessel Vasculitis. EULAR Paris, France: Ann Rheum Dis; 2014. p. 112-3. Acknowledgement: Acknowledgements: Joseph & Elizabeth Carey Endowment Fund and Lied Basic Science Research Development Award from University of Kansas Medical Center Disclosure of Interests: None declared